Dysfunctional Early Processing of Facial Expressions in Hazardous Drinkers: Evidence from an ERP Study. Issue 1 (December 2017) - Zhang, Hui; Jin, Yi; Chan, John; Yang, Feng-Chi; Cui, Fang
Abstract Chronic alcohol intoxication impairs multiple cognitive functions. According to the dual system model (DSM), the development of alcohol dependence (AD) involves the imbalance between the automatic-affective system and the reflective system. However, the cognitive functions of non-AD hazardous drinkers (HDs) remain unclear. The present study aimed to explore how the HDs process facial expressions differently from the healthy subjects. Sixteen HDs and seventeen control subjects (CSs) completed an emotional working memory (WM) task while the electroencephalogram (EEG) was recorded. We found that there was no significant group difference in behavioral performance between the two groups. In the ERP data, relative to the CSs, the HDs showed delayed latencies of P1 and N170. Moreover, the CSs showed significant differences between the amplitudes of neural/fear and disgust expressions while these differences were insignificant in the HDs. The current results suggest that the main deficits in the processing of facial expression in HDs existed in the early automatic-affective system instead of in the reflective system.